Identification of leptin resistance in patients with coronary artery disease and heart defects - E. Е. Gorbatovskaya; Yu. A. Dyleva; E. V. Belik; E. G. Uchasova; R. S. Tarasov; O. V. Gruzdeva (Российский кардиологический журнал)
Aim. To compare the incidence of leptin resistance (LR) in patients with acute and chronic coronary artery disease (CAD) and patients with acquired heart defects (AHD).Material and methods. The study included 234 patients: 114 patients with acute myocardial infarction (MI) and 120 patients with chronic CAD. The comparison group consisted of 48 patients with degenerative non-rheumatic AHD — aortic stenosis (AS). The control group consisted of 40 healthy volunteers. On the 1st day of hospitalization, the concentration of leptin and leptin receptor was measured, and the free leptin index (FLI) was assessed. LR was recorded at leptin >6,45 ng/ ml and FLI >25. Statistical data processing was carried out using the software package Statistica 10.0 and SPSS 17.0 for Windows.Results. Initially, LR in MI, chronic CAD and non-coronary disease was revealed in 64%, 56,2% and 25%, respectively. Significant differences in the incidence of LR were observed between patients with MI and chronic CAD relative to patients with AHD (p=0,02 and p=0,03, respectively), while no differences were found between patients with coronary pathology (p=0,82). Equation of patients for body mass index (BMI) did not affect the incidence of LR. High incidence of LR remained for patients with acute and chronic CAD, and amounted to 63% and 57,3%, respectively, while for patients with AS — 25%.Conclusion. Patients with acute and chronic CAD are characterized by a high LR incidence, in contrast to patients with AHD. The number of LR cases in patients with coronary pathology did not depend on BMI values, which indicates possible alternative leptin sources contributing the development of hyperleptinemia. In addition, studying the mechanisms underlying the leptin receptor decrease in CAD is necessary for adequate leptin effects and the prevention of LR.